Two-port myomectomy using bag-contained manual morcellation: A comparison with three-port myomectomy using power morcellation - Juseok Yang; Yong Jung Song; Yong Jin Na; Hwi Gon Kim (Elsevier, 2019)
Objectives: To evaluate the feasibility and safety of two-port myomectomy using bag-contained manual morcellation compared to three-port myomectomy using power morcellation. Material and methods: A retrospective chart review was conducted for 428 cases of either two-port or three-port laparoscopic myomectomy performed by single operator in the university hospital between January 2011 and December 2016. Results: The cohorts of three-port myomectomy with power morcellation was consisted of two hundred and forty-eight patients. One hundred and eighty patients underwent two-port myomectomy with manual morcellation in contained bag. Two-port group showed shorter hospital stay (5.16 ± 1.39 d vs. 4.83 ± 1.19 d, p = 0.001), less estimated blood loss (61.8 ± 58.2 mL vs. 50.2 ± 52.4 mL, p = 0.001), and higher hemoglobin level at postoperative day 1 (10.7 ± 1.17 g/dL vs. 11.0 ± 1.14 g/dL, p = 0.028) with statistical significance. Morcellation time (25.8 ± 9.30 min vs. 18.9 ± 10.11 min, p = 0.001) and total operative time (82.4 ± 30.19 min vs. 76.4 ± 25.47 min, p = 0.047) were also significantly shorter in two-port group. There were no identified spillages of fibroids, ruptures of specimen bag during manual morcellation in two-port myomectomy. In both groups, there were no cases of leiomyosarcoma diagnosed postoperatively. Conclusion: Two-port laparoscopic myomectomy with bag-contained manual morcellation is a feasible and safe alternative for three-port with power morcellation. Its surgical outcomes were shown to be superior to conventional laparoscopic myomectomy according to our study but further evaluation in near future is needed. Keywords: Contained morcellation, Morcellation, Laparoscopic myomectomy, Leiomyoma